The Effect of the Correlation of Public Debt on Some Indicators of Economic Stability in Iraq for the Period (2004-2023) - Eman Mudhafar Yousif (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research investigates the correlation between public debt and several indicators of economic stability in Iraq for the period from 2004 to 2023. It analyzes the development of both internal and external public debt in the Iraqi economy during this period and examines the relationship between public debt (internal and external) and key economic indicators, such as the Gross Domestic Product (GDP) and the inflation rate. The study utilizes standard statistical methods to analyze these relationships and provide a comprehensive overview of the effects of public debt on economic stability. The findings highlight a negative and significant impact of the growth rate of public debt on the inflation rate, both in the short term and long term, suggesting an inverse relationship between them. Similarly, the analysis shows a negative and significant effect of public debt growth on the unemployment rate, both in the short and long run, again indicating an inverse relationship. The study further discusses how the Iraqi government’s growing dependence on public debt, particularly external debt, can have an impact on the nation's economic policies. These results emphasize the complex dynamics between public debt and economic stability in Iraq, demonstrating how changes in debt levels can influence inflation and unemployment rates. The research underscores the need for effective debt management strategies to maintain economic stability and promote sustainable growth. Additionally, the findings suggest that public debt, if not managed carefully, can undermine key economic indicators and hinder the long-term stability of the economy, making it crucial for policymakers to consider the balance between debt levels and economic health.